OVERVIEW OF FISH AND SEAFOOD MARKET IN UKRAINE - SYDORENKO, Viktor (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the main indicators of the fish and seafood market in Ukraine. The structure of fish and seafood production in Ukraine since 2013 is considered, special emphasis is placed on its changes in the conditions of a full-scale war. A separate evaluation of the aquaculture products was carried out from the point of view the potential for restoration of the entire industry in the long term prospect. The dynamics of imports into Ukraine of products of group 3 "Fish, crustaceans and molluscs", quantitative and value indicators, the total balance of these products, changes in production by domestic companies and the main reasons in the dynamics of export and consumption were studied. The countries that are traditionally the leading suppliers of fish and seafood products to Ukraine are given. A high negative balance was noted in our country’s foreign trade in fish and seafood. The structural problems of the domestic fishery and aquaculture industry, which lead to insufficient volumes of production and a lower level of consumption compared to global trends are emphasized. A description of several indicators on the world market is provided, its development is assessed, and proposals for domestic producers are given. The article identifies main differences of the Ukrainian seafood market, including recent changes caused by environmental, economic, political trends and the war in Ukraine. The peculiarities of consumption the fish products in the domestic market are characterized, the growing role of aquaculture in the future development of the industry is highlighted. This article aims to provide domestic industrial enterprises, potential producers and relevant state authorities with information about current trends in the domestic fish and seafood market with the aim of identifying the potential of production in Ukraine and potentially reducing dependence on imports in this area.